Efficacy of cationic amphiphilic antihistamines on outcomes of patients treated with immune checkpoint inhibitors. (October 2022) - Chiang, Cho-Han; Chiang, Cho-Hung; Peng, Chun-Yu; Hsia, Yuan Ping; See, Xin Ya; Horng, Chuan-Sheng; Chang, Yu-Cheng; Shen, Xuan-Er; Wang, Shih-Syuan; Tsai, Tien-Chi; Chen, Yuan-Jen; Ma, Kevin Sheng-Kai; et al.
Abstract: Background: Cationic amphiphilic antihistamines have been shown to improve patient outcomes in immunogenic tumours, but whether they can augment and improve response to immunotherapy is unknown. We aim to evaluate the effect of cationic amphiphilic antihistamines in patients receiving immune checkpoint inhibitors (ICIs). Methods: We conducted a retrospective propensity score-matched cohort study at two tertiary referral centres in Taiwan between January 2015 and December 2021. Patients who received desloratadine, cyproheptadine, and ebastine were classified as cationic amphiphilic antihistamine users. The primary outcome was overall survival, and the secondary outcomes were progression-free survival and clinical benefit rate. Patients treated with cationic amphiphilic antihistamines were matched to patients who received non-cationic amphiphilic antihistamines based on variables including age, cancer type, stage, and history of allergic diseases. Results: A total of 734 ICI-treated patients were included. After matching, 68 cationic amphiphilic antihistamine and non-cationic amphiphilic antihistamine users remained for analysis. Compared with non-cationic amphiphilic antihistamine users, patients who received cationic amphiphilic antihistamines had a significantly longer median overall survival (24.8 versus 10.4 months; Log-rank, p = 0.018) and progression-free survival (10.6 versus 4.93 months; Log-rank, p = 0.004). The use of cationic amphiphilic antihistamines was associated with an approximately 50% lower risk of all-cause mortality (HR, 0.55 [95% CI: 0.34–0.91]). Survival benefits were not seen in patients who received cationic amphiphilic antihistamines before immune checkpoint blockade. These survival benefits were observed regardless of the generation of cationic amphiphilic antihistamines. Conclusion: The use of cationic amphiphilic antihistamines was associated with improved survival among patients treated with immunotherapy. Highlights: Study evaluating the effects of cationic amphiphilic antihistamines on immune checkpoint inhibitor therapy. Cationic amphiphilic antihistamines were associated with survival benefits. Effects not seen in patients who took cationic amphiphilic antihistamines before immune checkpoint inhibitor. Benefits observed regardless of the generation of cationic amphiphilic antihistamines.